Induction of 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase activity by fungal elicitor in cultures of Petroselinum crispum. - McCue, K F (1989)
The effects of a cell wall fraction of the fungus Phytophthora megasperma on the enzymatic activities of 3-deoxy-D-arabino-heptulosonate-7-phosphate (DAHP) synthase (EC 4.1.2.15) in extracts of cultured parsley cells (Petroselinum crispum) were examined. The specific activity of a plastidic form of DAHP synthase, designated DS-Mn by Ganson et al. [Ganson, R. J., d'Amato, T. A. & Jensen, R. A. (1986) Plant Physiol. 82, 203-210], was increased 2- to 3-fold in extracts of treated cells, with maximum induction occurring with 60 micrograms of fungal elicitor per ml after 6-8 hr. The cytosolic form of DAHP synthase, DS-Co, was unaffected by fungal elicitor. In the same experiments, phenylalanine ammonia-lyase activity (EC 4.3.1.5) increased, while no effect on isoforms of chorismate mutase (EC 5.4.99.5) was observed. The subcellular localization of the two DAHP synthase isoforms in parsley was confirmed by differential centrifugation. Prior treatment of cultures with actinomycin D or cycloheximide prevented the increase in DS-Mn activity, indicating transcriptional regulation.